Critical Thinking Among Field-Dependent and Field-Independent Students in Solving Mathematical Problems - Anton Adi Suryo Kusuma; Afifah Husna Karomah; Zohaib Hassan Sain (Jurnal Inovasi Matematika, 2026)
This study aims to analyze the cognitive styles of field-dependent and field-independent students in solving mathematical problems. This study employed a descriptive qualitative approach. The participants consisted of 32 fifth-grade students who completed the GEFT. Based on the classification results, four students representing field-independent and field-dependent cognitive styles were purposively selected as the main research subjects for the critical thinking test and interviews. The research instruments consisted of the Group Embedded Figure Test (GEFT) questions, critical thinking test questions, and interview questionnaires. Data validity was established through methodological triangulation and source triangulation. This study concluded that students with a field-independent (FI) cognitive style consistently demonstrated all critical thinking indicators (focus, reason, inference, situation & clarification, overview) in numeracy problem-solving tasks, as demonstrated by sequential solution steps, written verification, and contextual conceptual definitions. Conversely, Students with a field-dependent (FD) cognitive style demonstrated strengths in contextual understanding but encountered difficulties in documenting reasoning and drawing conclusions.